2010
DOI: 10.5851/kosfa.2010.30.6.905
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Retail Beef Yield Using Parameters Based on Korean Beef Carcass Grading Standards

Abstract: Two sets of data on carcass traits and beef cut parameters were used to investigate the relationships between carcass and beef cut measurements, which can be used to make predictions of retail cut percentages. One set had a total of 1,141 measurements of Hanwoo cattle of three different sex origins, which were slaughtered in an abattoir located at the National Institute of Animal Science, RDA, Korea from 1996 to 2008. To develop prediction models for retail cut percentage with higher accuracies than the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 11 publications
1
10
1
Order By: Relevance
“…One possible explanation about this lack of a correlation may be associated with fat content of the carcasses. Choy et al (2010) reported that retail cut percentage was highly correlated with body fat reserves and back fat thickness. On the other hand, Cicek et al (2016) suggested that, a negative and intermediate correlation (-0.51) was found between hot carcass weight and the percentage of tenderloin, sirloin, rib roast, rump, knuckle, round eye and topsideoutside flat (which was expressed as first degree retail cuts: FRC) in Holstein bull carcasses.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation about this lack of a correlation may be associated with fat content of the carcasses. Choy et al (2010) reported that retail cut percentage was highly correlated with body fat reserves and back fat thickness. On the other hand, Cicek et al (2016) suggested that, a negative and intermediate correlation (-0.51) was found between hot carcass weight and the percentage of tenderloin, sirloin, rib roast, rump, knuckle, round eye and topsideoutside flat (which was expressed as first degree retail cuts: FRC) in Holstein bull carcasses.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was reported that high correlation between (0.96) HCW and weights of total retail cuts [9] . In another study, it was detected high correlation (0.94) between CCW and weights of total retail cuts [10] . It was determined that increase in HCW or CCW, increases REA and FT linearly [13] .…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies, which used by similar methods [7,9,10,12] . CCW was used instead of HCW in other research except Chen et al [9] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations